Ten questions to ask yourself before writing a teaching case. Part 1 : RSM CDC case writing training material - Yue, Tao, active 2024 (London : Rotterdam School of Management, Erasmus University, 2024)
When it comes to creating teaching cases, clear writing goes hand in hand with clear thinking. To get ready for this task, it’s a good idea to ask yourself ten important questions before you start writing. These questions help you make sure your teaching case is effective. By thinking about these questions, you’ll be better prepared to write a great teaching case that gets your message across clearly. The answers to these questions can be found in training material part 2: How to Write a Good Teaching Case.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Case method -- Case studies; Lesson planning -- Case studies; Teaching -- Aids and devices -- Authorship -- Case studies